SOME ASSESSMENTS OF THE PUBLICATION ACTIVITY OF SCIENTISTS OF THE NATIONAL STATE UNIVERSITY OF PHYSICAL CULTURE, SPORTS AND HEALTH AFTER P.F. LESGAFT - Shegelman I. R., Kirilina V. M., Vasilyev A. S. (Pedagogy and psychology: development prospects, 2019)
according to the knowledge base of the Russian index of scientific citation, some estimates of the publication activity of scientists of the National State University of Physical Culture, Sports and Health named after P.F. Lesgaft
Keywords: физическая культура и спорт; патент; индекс Хирша; цитирование; публикации; база знаний; publications; knowledge base; patent; physical education and sport; Hirsch index; citation